RESOLUSI KONFLIK KAUM KAPITALIS DAN BURUH MELALUI PRODUK BAY’ MURA - Supriyadi, Ahmad (AL-TAHRIR, 2014)
Conflicts have occurred in societies since early time in human civilization and continue up to the present time. Conflicts may happen between two individuals or two groups. But there also conflicts of class between creditors and debtors which has not been resolved. They often dispute over a particular issue but do not find an effective media to tackle it. Sharia banking, a new emerging Islamic system of bank, seems to offer a good answer to this problem. This article aims to explain this financial institution and its products and examines the ways in which its products operate and contribute to solve the problem. There are two products of Syari’ah Banking to solve such a classic problem between debtors and creditors; bay’ al-murabahah and  mudarabah. The first product helps mediate capital owners and debtors through a definite mechanism facilitated by Shari’a bank. Through the second product, debtors can enhance their life standard by purchasing stock and share the profits while creditors or capital owners can sell their stock to collect fund without making a bank loan. This is the solution that Islamic banking system contributes.